Impact of load variation on power system stability and performance of power system stabilizers: A case study of Peerdawd gas power station, Iraq - Hameed, Jawad Hamad; Hashim, Wassan Adnan; Derbel, Nabil (Institute of Advanced Engineering and Science, 2023)
Variable load on the station refers to the fluctuating load on a power plant due to erratic consumer demands. It is known to have an effect on the performance of power system stabilizers, particularly in damping inter-area oscillation. This paper examines how two power system stabilizer (PSS) models and various load conditions affect a power system's voltage and power stability. A dynamic model of the power system station, based on the real case study of the Peerdawd gas power station in north Iraq (PPGS), is utilized to investigate the response of both steady-state and transient-state models: the aggregated excitation control system (Ex2100) and the power system stabilizer (PSS2B). The impact of load variation on voltage stability under normal situations and during disturbances is discussed. Furthermore, the effect of reactive power support from the power plant on the input of the two PSS models is analyzed and discussed. The paper employs a MATLABTM/Simulink-based simulation program, and the results contribute to understanding how load variation influences system damping based on PSS.